Spirituality for our global community beyond traditional religion to a world at peace - Helminiak, Daniel A. (Lanham, Md. : Rowman & Littlefield Publishers, 2008)
"In this groundbreaking book, Daniel A. Helminiak provides a crucial spiritual option - a middle path between society's secular materialism and traditional religion's other worldly focus and institutional dogmatism. The functional atheism of contemporary society doesn't satisfy the human desire for lasting meaning and value. But parochial, inflexible religious beliefs can foster personal, local, and global conflicts in a postmodern world of pluralism, globalization, and respect for science and progress."--BOOK JACKET.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Spirituality; Globalization -- Religious aspects; Spiritualität; Globalisierung; BODY, MIND & SPIRIT / Inspiration & Personal Growth; BODY, MIND & SPIRIT / Spirituality / General; RELIGION / Christianity / General; RELIGION / Devotional; RELIGION / Spirituality; Electronic books